2020
DOI: 10.1149/1945-7111/abd003
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection in Chloride Environments of Nanosilica Containing Epoxy Powder Coatings with Defects

Abstract: This paper describes the use of innovative, nanosilica containing epoxy powder coatings for the corrosion protection of steel. Two types of nanosilica particles (hydrophilic -HL-and hydrophobic -HB-) were mixed by ball milling with the powders (0.75 wt.%). The adequate homogeneity and embedding of nanoparticles were verified by transmission electron microscopy.The corrosion performance of the coatings as-received, and with HL and HB additions, were analyzed in 3.5 wt.% NaCl solutions. The mechanism and rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Different studies are found in the literature regarding improvement of protection given by the coatings to the metal substrates in aggressive environments. Some work has been able to obtain mechanical improvements in coatings with different types of inert reinforcements [6,7]. At the same time, other authors have focused more on manufacturing anticorrosive coatings with the addition of smart corrosion inhibitors that present different protection mechanisms when the corrosive agents appear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies are found in the literature regarding improvement of protection given by the coatings to the metal substrates in aggressive environments. Some work has been able to obtain mechanical improvements in coatings with different types of inert reinforcements [6,7]. At the same time, other authors have focused more on manufacturing anticorrosive coatings with the addition of smart corrosion inhibitors that present different protection mechanisms when the corrosive agents appear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been recently reported that mesoporous nanosilica particles can exert an inhibitory effect against delamination [10]. As far as nanoparticles are concerned, their direct effect in metalcoating adhesion improvement and polymer crosslinking cannot be ignored [6], as well as the improvement of strength and barrier properties of coating [10]. However, the use of nanosilica as smart carriers for corrosion protection has been strongly developed in recent years, acting as reservoir for functional species (inhibitor/self-healing agent).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic inhibitors are one contemporary method for protecting metals against acidic, neutral and basic corrosion. Different organic materials, mainly those rich in oxygen, sulfur and nitrogen heteroatoms, have been selected as a good strategy for protecting MS in a wide variety of acidic environments, including hostile chloride ions (Mazumder et al , 2014; Zou et al , 2014; Bouanis et al , 2016; Zuo et al , 2017; Fernández-Álvarez et al , 2020; Xia et al , 2021). In acidic medium, the positive charge of steel surface allows for either direct coordination with the electronegative functional moieties of organic inhibitors or indirect adsorption of inhibitor cations species to form self-assembled layers via a synergistic effect with chloride ions that improve anticorrosion property (Mazumder et al , 2014; Elshakre et al , 2017; Li et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion behavior and mechanisms of defective coated steel have been studied extensively. Fernández-Álvarez et al [8] proposed that the corrosion proceeds by anodic undermining when defective coatings are immersed in 3.5 wt.% NaCl solutions. As the reaction proceeds, oxygen is consumed in cathodic reduction, and corrosion products form in the defect, hindering the transportation of dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%